Enhancing Politeness and Cultural Adaptation in BIPA Education: A Community Service Initiative for Foreign Students - Tiawati, Refa Lina; Harahap, Safinatul Hasanah; Kurnia, Maya Dewi; Nazriani, Nazriani; Annisa, Witri (Bhandar: Harvesting Community Service in Asia, 2024)
This community service initiative was conducted to help foreign students in the BIPA (Indonesian for Foreign Speakers) program develop a deeper understanding of cultural discourse in their daily interactions. Using a hands-on, experiential learning approach, students were guided in mastering culturally appropriate speech acts such as making requests, offering invitations, providing advice, and pleading, all in accordance with Indonesian social norms. The results of the project indicate significant improvements in the students' ability to communicate politely and effectively, reflecting their increased awareness of Indonesian cultural etiquette. This enhanced communication competence has facilitated smoother adaptation to the social environment in Indonesia, helping students build better relationships and integrate more fully into the local community.